Penegakan Hukum Bagi Pedagang Usaha Mikro, Kecil Dan Menengah Terhadap Para Pelaku Usaha Monopoli - Rina Shahriyani Shahrullah; Henry Hadinata Cokro (Universitas Internasional Batam, 2020)
This research was conducted for the purpose of ascertaining law enforcements for Small and Medium Enterprises (SMEs) business actors in Indonesia based on Law Number 55 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. It also analyzes the role of government in providing enforcements to small and Medium Enterprises. In this study, normative legal research was used. It found that the legal protection of small businesses competition in Indonesia is a manifestation of the implementation of economic democracy that contains the principles of justice and togetherness to encourage creating opportunities for every businessman in a healthy competition environment. It also found that healthy competition aims to avoid a monopoly of certain business actors only, but it could provide business opportunities for Small and Medium Enterprises business actors to enlarge their business.